Social Psychology of Mental Health: The Social Structure and Personality Perspective - Sánchez Moreno, Estéban; Barrón López de Roda, Ana (The Spanish Journal of Psychology, 2003)
Previous research has revealed a persistent association between social structure and mental health. However, most researchers have focused only on the psychological and psychosocial aspects of that relationship. The present paper indicates the need to include the social and structural bases of distress in our theoretical models. Starting from a general social and psychological model, our research considered the role of several social, environmental, and structural variables (social position, social stressors, and social integration), psychological factors (self-esteem), and psychosocial variables (perceived social support). The theoretical model was tested working with a group of Spanish participants (N = 401) that covered a range of social positions. The results obtained using structural equation modeling support our model, showing the relevant role played by psychosocial, psychological and social, and structural factors. Implications for theory and intervention are discussed.
Keywords: mental health; social structure; social support; self-esteem; social integration